2007
DOI: 10.2471/blt.06.039081
|View full text |Cite
|
Sign up to set email alerts
|

roles of laboratories and laboratory systems in effective tuberculosis control

Abstract: Laboratories and laboratory networks are a fundamental component of tuberculosis (TB) control, providing testing for diagnosis, surveillance and treatment monitoring at every level of the health-care system. New initiatives and resources to strengthen laboratory capacity and implement rapid and new diagnostic tests for TB will require recognition that laboratories are systems that require quality standards, appropriate human resources, and attention to safety in addition to supplies and equipment. To prepare t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 16 publications
(10 reference statements)
0
44
0
1
Order By: Relevance
“…These red particles sometime match with tubercle bacilli and might cause false positive results (Kubica and Dye, 1967;Van et al, 2005). Such misleading diagnosis can be reduced by incorporating TB culture which is a more reliable and accurate method for TB diagnosis (Ridderhof et al, 2007). Moreover, the TB culture allows diagnosis of early stage of the disease and the identification of the mycobacterium species, which are not possible with sputum microscopy (Gandhi et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…These red particles sometime match with tubercle bacilli and might cause false positive results (Kubica and Dye, 1967;Van et al, 2005). Such misleading diagnosis can be reduced by incorporating TB culture which is a more reliable and accurate method for TB diagnosis (Ridderhof et al, 2007). Moreover, the TB culture allows diagnosis of early stage of the disease and the identification of the mycobacterium species, which are not possible with sputum microscopy (Gandhi et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Observers have concluded that dramatic improvements in baseline capacity are necessary to meet anticipated surveillance and treatment targets. 81,82,83,84,85 In 2005, the World Health Assembly passed a resolution requesting the DirectorGeneral "to implement and strengthen strategies for the effective control of, and management of persons with, drug-resistant tuberculosis." The 2006 Global Plan to Stop TB stresses the importance of laboratory services, stating that "every country should have a well-resourced and fully functioning national reference laboratory."…”
Section: Expanding Laboratory Capacitymentioning
confidence: 99%
“…Approximation of experimental density distribution of AFM visualized aptamers with heights ρ(h) (1) was carried out using function (2). It was obtained from this approximation that visualized objects form a group of objects with the maximum height h max (apt)=(0.9±0.1) nm, and a full width at half maximum was W=(0.5±0.1) nm.…”
mentioning
confidence: 99%
“…Approximation of experimental density distribution of complexes with heights ρ(h) (1) was carried out using function (2). As a result, maximum heights of the visual ized complexes were 1) h max ( protein/apt)=(1.6±0.1) nm after incubation in 0.8×10 -9 M gp120 solution and 2) h max ( protein/ apt)=(1.4±0.1) nm after incubation in 0.8×10 -11 M gp120 solution.…”
mentioning
confidence: 99%